A case report: Clinical application of celiac plexus block in bile duct interventional procedures. Issue 27 (July 2016) - Karm, Myong-Hwan; Cho, Hyun-Seok; Lee, Jae-Young; Bae, Heon-Yong; Ahn, Ho-Soo; Kim, Yeon Ju; Leem, Jeong-Gil; Choi, Seong-Soo
Abstract : Abstract: Although percutaneous transhepatic biliary drainage (PTBD) and tract dilatation (TD) are very painful procedures, almost all of those procedures have been conducted under local anesthesia and opioid injection due to the lack of manpower and time. Celiac plexus block (CPB) is an interventional technique used for diagnostic and therapeutic purposes in the treatment of abdominovisceral pain. CPB decreases the side effects of opioid medications and enhances analgesia from medications. We present the case of a patient who underwent PTBD and TD under CPB in order to reduce procedure-related abdominal pain. CPB can be a useful alternative technique for pain management during and after biliary interventional procedures, although CPB-induced complications must always be kept in mind.